High-accuracy simultaneous measurement of surface profile and film thickness using line-field white-light dispersive interferometer. (February 2021) - Guo, Tong; Zhao, Guanhua; Tang, Dawei; weng, Qianwen; Sun, Changbin; Gao, Feng; Jiang, Xiangqian
Highlight: Simultaneous measurement of surface profile and thickness of the film structure Achieve high-accuracy phase of spectral signal with phase-shifting method Profile reconstruction error rectified using line-by-line calibration method Measurement noise immunity enhanced with single wavenumber method Abstract: White-light dispersive interferometry (WLDI) is an instantaneous, high-resolution optical metrological technique for measuring precise and complicated surfaces. This method enables nondestructive inspection of transparent-film-structure devices that are widely used in semiconductor packaging. We propose in this paper to use a home-built WLDI system with line-by-line spectral calibration, phase-shifting algorithm, and single-wave-number method for high-accuracy, simultaneous measurements of surface profiles and film thickness. By calibrating the relationship between wave-number and pixel position on each line of a two-dimensional detector, the line-by-line calibration method improves the measurement accuracy by correcting the spectral distortion caused by the optical system. Moreover, the spectral signal phase is obtained by the phase-shifting algorithm instead of by the Fourier transform method. The single-wave-number method is applied to the computation process by introducing the fringe order, and the measurement result indicates that it enhances the system immunity to environmental noise. A 1.806-µm-high standard step and a 1052.2-nm-thick standard film are measured to verify the system performance and show that the system is highly accurate and reliable.